Proposal for a teaching game for teaching water resource conservation (Research, Society and Development, 2021)
In view of all that we can understand of the importance of the different ways of working with the contents in science and biology teaching, a way of studying in the biology classes the content of Ecology, especially the conservation of water resources, was thought of in a more playful way. Therefore, this work aims to develop a didactic game about the use of water as a resource, through the creation of ecological awareness and intelligent consumption for the conservation of water resources. In order to carry out the construction of the didactic game, data were collected on the bibliographic review on the theme and on the creation of didactic games. In this work the didactic game developed was made through the water content, it is a board game in which the players will walk from the exit to the arrival, where pins, dice and cards will be used, in which the player will have questions or some traps, advance houses, return houses, stay without playing a round, among others. The prospect of using this game is to be one more way of learning about water content, especially in terms of conserving water resources where it would be helping the student to create an ecological awareness and sustainability and making the understanding of the importance of using water available. water resource. The applicability of the game must be done before or after explaining the content, for high school students. In this way the student can have a better memorization of the subject and have a change in habits and thoughts.